Teacher as Social Context (TASC) Questionnaire in the Spanish Setting : Teacher Version - Iglesias García, María Teresa (Colegio Oficial de Psicólogos de Madrid, 2020)
This study pioneered the construction or adaptation of a Spanish version of the Teacher as Social Context (TASC) Questionnaire. The current study included a sample of 410 secondary education teachers in Spain. A confirmatory factor analysis was performed using the maximum likelihood estimation; the factorial invariance of the TASC-Spanish teacher measure across genders was analyzed using a multi-group confirmatory factor analysis. Finally, correlational analyses between the three TASC scales (involvement, structure, and autonomy support) and behavioral and emotional engagement were run. The results of this research confirmed the structure of the original instrument maintaining the three basic domains. The measurement model also proved to be invariant across gender. Besides, this study supports the assumption that teachers' perceptions of their own activity to fulfil students' basic psychological needs show a relationship with students' emotional and behavioural engagement, being teachers' involvement the most determinant domain.